Efficiency of the newest sterile substrate production technology for oyster cultivation. (November 2019) - Soldatenko, A; Devochkina, N; Ivanova, M
Abstract: The article conducted production tests and developed parameters of the innovative technology for substrate preparation under sterile conditions for the cultivation of oyster mushrooms. Oyster mushroom is the second largest industrial mushroom culture, which belongs to the group of wood-destroying mushrooms. World production of oyster mushrooms is about 1.5 million tons per year. Its cultivation is practiced in Italy, France, Belgium, the Netherlands, Japan, and Taiwan. Fruit bodies of oyster mushrooms have high nutritional and medicinal value. Biological features of a culture allow its production under conditions of both specialized cultivation facilities and in adapted premises, thereby solving the problem of their effective use. The industrial mushroom production in the Russian Federation is growing due to the construction of industrial complexes for mushroom cultivation. According to experts, the expansion of the cultivation of oyster mushrooms with the use of contemporary technologies and technological equipment is a very promising business for our country. The total annual production of oyster mushrooms does not exceed 4-5 thousand tons, which does not even provide 5-6% of the required domestic demand. In Russia, mushroom producers, farmers, and subsidiary farms are constantly looking for a solution to the problem of acquiring high-quality raw materials, organizing the full technological cycle of production, choosing the technology for preparing the substrate and growing the fruit bodies of the mushroom that would ensure the economic efficiency of the production of fruit bodies of mushrooms. When growing oyster mushrooms in small enterprises, the following simplest methods of processing raw materials are used: soaking in hot water without temperature control and without optimal processing time, respectively. The quality of the substrate prepared in this way is very low, and the level of the resulting crop does not provide cost-effective results, which leads to the cessation of the mushroom production. Therefore, the latest technological and technical solutions to virtually solve the issues of introducing new equipment for the production of high-quality substrate are relevant and important. This will allow to obtain stable yields and effectively lead the production of significant low-calorie fresh protein products, namely oyster mushroom bodies.